The Effects of Using a Guidance Activities Package to Develop Health Literacy of Nursing Students in The Royal Thai Army Nursing College - Kanchanakomol, Savangjit (Journal of The Royal Thai Army Nurses, 2021)
The purposes of this study were: (1) to compare health literacy of nursing students before and after receiving a guidance activities package and (2) to compare health literacy of an experimental group receiving the guidance activities package and a control group receiving regular guidance. The samples consisted of 40 second-year nursing students in an academic year 2019, who volunteered to participate in the research project. Then, a method of simple random sampling was conducted to separate the samples into two groups, the experimental group and the control group, with 20 students in each group. The experimental group received the guidance activities package to develop health literacy for 12 sessions with duration of 50 minutes in each session, while the control group received normal guidance. The instruments included: (1) the guidance activities package to develop health literacy, and (2) the health literacy questionnaire with a reliability of .83. The statistics employed for this analysis were percentile, medium, standard deviation and t-test. Research findings revealed as follow; (1) after receiving the guidance activities package, health literacy of nursing students in the experimental group was higher with statistical significance at a level of .01 and (2) the health literacy of the nursing students in the experimental group who received the guidance activities package was higher than the nursing students in the control group who received normal guidance with statistical significance in a level of .01.